Tuning the transcriptional response to hypoxia by inhibiting Hypoxia-inducible Factor (HIF) prolyl and asparaginyl hydroxylases - Chan, Mun Chiang; Ilott, Nicholas E.; Schödel, Johannes; Sims, David; Tumber, Anthony; Lippl, Kerstin; Mole, David R.; Pugh, Christopher W.; Ratcliffe, Peter John; Ponting, Chris P.; Schofield, Christopher J. (Journal of Biological Chemistry, 2016)
The hypoxia-inducible factor (HIF) system orchestrates cellular responses to hypoxia in animals. HIF is an α/β-heterodimeric transcription factor that regulates the expression of hundreds of genes in a tissue context-dependent manner. The major hypoxia-sensing component of the HIF system involves oxygen-dependent catalysis by the HIF hydroxylases; in humans there are three HIF prolyl hydroxylases (PHD1-3) and an asparaginyl hydroxylase (factor-inhibiting HIF (FIH)). PHD catalysis regulates HIFα levels, and FIH catalysis regulates HIF activity. How differences in HIFα hydroxylation status relate to variations in the induction of specific HIF target gene transcription is unknown. We report studies using small molecule HIF hydroxylase inhibitors that investigate the extent to which HIF target gene expression is induced by PHD or FIH inhibition. The results reveal substantial differences in the role of prolyl and asparaginyl hydroxylation in regulating hypoxia-responsive genes in cells. PHD inhibitors with different structural scaffolds behave similarly. Under the tested conditions, a broad-spectrum 2-oxoglutarate dioxygenase inhibitor is a better mimic of the overall transcriptional response to hypoxia than the selective PHD inhibitors, consistent with an important role for FIH in the hypoxic transcriptional response. Indeed, combined application of selective PHD and FIH inhibitors resulted in the transcriptional induction of a subset of genes not fully responsive to PHD inhibition alone. Thus, for the therapeutic regulation of HIF target genes, it is important to consider both PHD and FIH activity, and in the case of some sets of target genes, simultaneous inhibition of the PHDs and FIH catalysis may be preferable.
CRIS-Team Scopus Importer:2024-05-13